2020
DOI: 10.3389/fchem.2020.00452
|View full text |Cite
|
Sign up to set email alerts
|

Supported Molybdenum Carbide and Nitride Catalysts for Carbon Dioxide Hydrogenation

Abstract: Catalysts based on molybdenum carbide or nitride nanoparticles (2-5 nm) supported on titania were prepared by wet impregnation followed by a thermal treatment under alkane (methane or ethane)/hydrogen or nitrogen/hydrogen mixture, respectively. The samples were characterized by elemental analysis, volumetric adsorption of nitrogen, X-ray diffraction, and aberration-corrected transmission electron microscopy. They were evaluated for the hydrogenation of CO 2 in the 2-3 MPa and 200-300 • C ranges using a gas-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…As regards to the conversion, it can be observed that while -Mo2C catalysts showed a quite stable profile, the other samples displayed some changes along time on stream. The conversion obtained was in the range 3 -5 % and the values followed the trend Cu/Mo2C > Cu/Cs/Mo2C > -Mo2C > Cs/Mo2C which are in fair agreement with the reported conversion levels for this challenging reaction [ 15]. Moreover, the main compound obtained was methanol and the selectivity reached 50-65 % following a slightly different trend to that of the conversion: Cu/Mo2C > -Mo2C > Cu/Cs/Mo2C > Cs/Mo2C.…”
Section: Resultssupporting
confidence: 88%
“…As regards to the conversion, it can be observed that while -Mo2C catalysts showed a quite stable profile, the other samples displayed some changes along time on stream. The conversion obtained was in the range 3 -5 % and the values followed the trend Cu/Mo2C > Cu/Cs/Mo2C > -Mo2C > Cs/Mo2C which are in fair agreement with the reported conversion levels for this challenging reaction [ 15]. Moreover, the main compound obtained was methanol and the selectivity reached 50-65 % following a slightly different trend to that of the conversion: Cu/Mo2C > -Mo2C > Cu/Cs/Mo2C > Cs/Mo2C.…”
Section: Resultssupporting
confidence: 88%
“…In regard to the conversion, it can be observed that while β-Mo 2 C catalysts showed a quite stable profile, the other samples displayed some changes along time on stream. The conversion obtained was in the range 3%-5% and the values followed the trend Cu/Mo 2 C > Cu/Cs/Mo 2 C > β-Mo 2 C > Cs/Mo 2 C, which are in fair agreement with the reported conversion levels for this challenging reaction [15]. Moreover, the main compound obtained was methanol and the selectivity reached 50%-65%, following a slightly different trend to that of the conversion: Cu/Mo 2 C > β-Mo 2 C > Cu/Cs/Mo 2 C > Cs/Mo 2 C. Unlike the conversion behavior, the selectivity profiles were quite stable for all the catalysts except for the sample Cu/Cs/ Mo 2 C. The other detected products were CO and CH 4 , with minor contributions of ethanol, which was below 0.2% except for the catalyst Cs/Mo 2 C that was around 2% and is included in Figure 1.…”
Section: Resultssupporting
confidence: 88%
“…In addition, other combinations of Cu and metal/metal oxides have been explored extensively in the methanol synthesis field, such as Cu/Mg/Al [30], Cu/ZnO/ZrO 2 [31,32]. For comparison's sake, the performances of other Mo 2 C related catalysts have also been listed in Table 1 [15,33]. As can be seen, although Cu-based catalysts are suitable for CO 2 hydrogenation, an efficient catalyst exhibiting high selectivity, conversion, and functional stability towards methanol synthesis at low pressure (less than 50 bar) has not been developed yet [31].…”
Section: Resultsmentioning
confidence: 99%
“…1 kg catalyst) 18 . The activity and selectivity of CO 2 hydrogenation catalysts based on molybdenum carbide can be affected by the C/Mo ratio in the catalyst 19 , 20 . According to density functional theory (DFT) calculations, the Mo-terminated surface of β-Mo 2 C is more reactive for the dissociation of CO 2 than the C-terminated surface 16 , and H 2 dissociation is most favored on the Mo-terminated (001) facet, compared to the C-terminated or mixed Mo/C-terminated facets 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%